2015
DOI: 10.1016/j.jconrel.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sustained, low-dose intraperitoneal cisplatin improves treatment outcome in ovarian cancer mouse models

Abstract: Intraperitoneal (IP) chemotherapy for ovarian cancer treatment prolongs overall survival by 16 months compared to intravenous chemotherapy but is not widely practiced due to catheter-related complications and complexity of administration. An implantable, nonresorbable IP microdevice was used to release chemotherapeutic agent at a constant rate of approximately 1.3 µg/hour in vitro and 1.0 µg/hour in vivo. Studies conducted in two orthotopic murine models bearing human xenografts (SKOV3 and UCI101) demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…An implantable, nonresorbable IP micro-device was developed to release a chemotherapeutic agent to the peritoneal cavity at a constant rate. 10 Preclinical studies showed reduced toxicity by the controlled drug release from this micro-device with similar efficacy outcomes to frequent IP bolus doses. Current efforts related to IP drug delivery are mainly to provide a depot for sustained release of chemotherapeutic agents in the peritoneal tumor environment, thus increasing local drug levels while reducing systemic exposure.…”
mentioning
confidence: 79%
“…An implantable, nonresorbable IP micro-device was developed to release a chemotherapeutic agent to the peritoneal cavity at a constant rate. 10 Preclinical studies showed reduced toxicity by the controlled drug release from this micro-device with similar efficacy outcomes to frequent IP bolus doses. Current efforts related to IP drug delivery are mainly to provide a depot for sustained release of chemotherapeutic agents in the peritoneal tumor environment, thus increasing local drug levels while reducing systemic exposure.…”
mentioning
confidence: 79%
“…Additionally, the work by Colin et al [36] does estimate the changes in tumour volume based on a PDPD link suggested by Ait-Oudhia et al [65]. Given the recent interest in metronomic chemotherapy in the context of IP chemotherapy [66], extending models to include growth and cell survival might become more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…who developed a delivery device for IP administration of cisplatin. [ 155 ] The device design was based on in vitro work by the group that demonstrated that sustained low doses of cisplatin produced better killing of ovarian cancer cells than intermittent dosing. [ 156 ] The devices used were fabricated from poly‐ l ‐lactic acid and consisted of a spherical chamber and cap.…”
Section: Advanced Delivery Solutionsmentioning
confidence: 99%
“…The cap had a circular orifice with a diameter of 180 μm, chosen to control cisplatin release based on its solubility and diffusivity. [ 155 ] The devices were loaded with 5 mg cisplatin powder. The device was tested in mice, using weekly IP bolus injections (5 mg kg −1 ) as a control.…”
Section: Advanced Delivery Solutionsmentioning
confidence: 99%
See 1 more Smart Citation